MicroRNA‐141‐3p targets DAPK1 and inhibits apoptosis in rat ovarian granulosa cells. (22nd May 2017) - Li, Dandan; Xu, Duo; Xu, Ying; Chen, Lu; Li, Chunjin; Dai, Xiaowei; Zhang, Lili; Zheng, Lianwen
Abstract : The polycystic ovary syndrome (PCOS) is a complex and heterogeneous endocrine disorder. MicroRNAs negatively regulate the expression of target genes at posttranscriptional level by binding to the 3′ untranslated region of target genes. Our previous study showed that miR‐141‐3p was dramatically decreased in the ovaries of rat PCOS models. In this study, we aimed to characterize the target of miR‐141‐3p in rat ovarian granulosa cells. 3‐(4, 5‐Dimethylthiazol‐2‐Yl)‐2, 5‐Diphenyltetrazolium Bromide (MTT) assay showed that cell viability was dramatically increased when miR‐141‐3p was overexpressed but was decreased when miR‐141‐3p was interfered. Flow cytometry showed that cell apoptotic rate was dramatically decreased when miR‐141‐3p was overexpressed but was increased when miR‐141‐3p was interfered. Bioinformatics analysis predicted that death‐associated protein kinase 1 (DAPK1) might be the target gene of miR‐141‐3p because the 3′ untranslated region of DAPK1 contains sequences complementary to microRNA‐141‐3p. Transfection with miR‐141‐3p mimics and inhibitor into granulosa cells showed that both DAPK1 mRNA and protein levels were negatively correlated with miR‐141‐3p level. Dual‐luciferase reporter assay established that DAPK1 was the target of miR‐141‐3p. Taken together, our data indicate that miR‐141‐3p may inhibit ovarian granulosa cell apoptosis via targeting DAPK1 and is involved in the etiology of PCOS.